Novel hydrogen chemisorption properties of amorphous ceramic compounds consisting of p-block elements: exploring Lewis acid–base Al–N pair sites formed in situ within polymer-derived silicon–aluminum–nitrogen-based systems. Issue 5 (14th January 2021) - Tada, Shotaro; Asakuma, Norifumi; Ando, Shiori; Asaka, Toru; Daiko, Yusuke; Honda, Sawao; Haneda, Masaaki; Bernard, Samuel; Riedel, Ralf; Iwamoto, Yuji
Abstract : This paper reports the relationship between the H2 chemisorption properties and reversible structural reorientation of the possible active sites around Al formed in situ within polymer-derived ceramics (PDCs) based on an amorphous Si–Al–N system. Abstract : This paper reports the relationship between the H2 chemisorption properties and reversible structural reorientation of the possible active sites around Al formed in situ within polymer-derived ceramics (PDCs) based on an amorphous silicon–aluminum–nitrogen (Si–Al–N) system. Al-modified polysilazane, as a ceramic precursor, was first pyrolyzed at 1000 °C under flowing ammonia to generate a Si–Al–N-based ceramic. XRD and HRTEM analyses confirmed the amorphous state of the titled ceramics. N2 adsorption–desorption isotherm measurements and HAADF-STEM observation of amorphous SiAlN indicated that Al-incorporation in the early step of the process led to the generation of micro/mesoporosity in the amorphous ceramic with nanopores of 1 to 4 nm in size. XPS and pyridine sorption infra-red spectroscopy analyses revealed the in situ formation of Lewis acidic Al sites within the amorphous Si–Al–N surface network. As a result, the Si–Al–N compound was highly moisture sensitive. Then, to investigate the intrinsic properties of the highly reactive Al sites, the Si–Al–N compound was pretreated at 400–800 °C under an inert atmosphere. Temperature-programmed-desorption (TPD)-mass spectroscopy analysis of the pre-treated sample after H2 treatment above 100 °C resulted in the detection of a broad H2 desorption peak at around 100 to 350 °C. The H2 desorption peak intensity apparently increased when H2 treatment was performed at 150 °C, and the activation energy for H2 desorption was determined to be 44 kJ mol −1 . 27 Al MAS NMR spectroscopic analysis for the pre-treated sample showed reversible local structure reorientation around reactive Al nuclei, and formation and deformation of 5-fold coordinated Al by H2 chemisorption and desorption, respectively. In addition, the CO2 hydrogenation reaction on the pre-treated sample was successfully demonstrated by TPD measurements after exposure to a mixed gas of H2 and CO2 with a 4 : 1 ratio at 400 °C. These results suggest that highly distorted 4-fold coordinated Al serves as a Lewis acid–base Al–N pair site to promote H2 chemisorption at T > 100 °C followed by formation of a hydrogenated 5-coordinated Al unit where CO2 hydrogenation proceeds at T = 400 °C.